Green management : a new paradigm in the world of business - Gupta, Swati; Taneja, Sanjay; Özen, Ercan; Sood, Kiran; Grima, Simon (Emerald Publishing Limited, 2024)
Environmental concerns are at the forefront of governments, NGOs, businesses and organizations around the world. Green management has prompted questions about existing management research traditions' profit-oriented structures emphasising the price of economic progress. Green Management brings together works by specialists from different disciplines and continents to reflect on the nexus between Green Management and its impact on businesses. The chapters examine Green Finance, Green HRM, Green Supply Chain Management, Green Technology and Green Marketing and how they might be used to investigate the effects of Green Business, especially for managers and policymakers. Emerald Studies in Finance, Insurance, and Risk Management provides a platform for authors to explore, analyse and discuss current and new financial models and theories, and engage with innovative research on an international scale. Subjects of interest may include banking, accounting, auditing, compliance, sustainability, behaviour, management, and business economics.
Includes index.
Keywords: Sustainable development.; Business & Economics, Green Business.; Management and management techniques.; Business and the environment; green approaches to business.; elektronické knihy; electronic books